Broadband Terahertz Photonic Integrated Circuit with Integrated Active Photonic Devices - Amlan Kusum Mukherjee (MDPI AG, 2021)
Present-day photonic terahertz (100 GHz–10 THz) systems offer dynamic ranges beyond 100 dB and frequency coverage beyond 4 THz. They yet predominantly employ free-space Terahertz propagation, lacking integration depth and miniaturisation capabilities without sacrificing their extreme frequency coverage. In this work, we present a high resistivity silicon-on-insulator-based multimodal waveguide topology including active components (e.g., THz receivers) as well as passive components (couplers/splitters, bends, resonators) investigated over a frequency range of 0.5–1.6 THz. The waveguides have a single mode bandwidth between 0.5–0.75 THz; however, above 1 THz, these waveguides can be operated in the overmoded regime offering lower loss than commonly implemented hollow metal waveguides, operated in the fundamental mode. Supported by quartz and polyethylene substrates, the platform for Terahertz photonic integrated circuits (Tera-PICs) is mechanically stable and easily integrable. Additionally, we demonstrate several key components for Tera-PICs: low loss bends with radii ∼2 mm, a Vivaldi antenna-based efficient near-field coupling to active devices, a 3-dB splitter and a filter based on a whispering gallery mode resonator.